Case report: A single novel calpain 3 gene variant associated with mild myopathy - Massucco, Sara; Fossa, Paola; Fiorillo, Chiara; Faedo, Elena; Gemelli, Chiara; Barresi, Rita; Ripolone, Michela; Patrone, Serena; Gaudio, Andrea; Mandich, Paola; Gotta, Fabio; Baratto, Serena; et al. (Frontiers in Genetics, 2024)
Recessively inherited limb-girdle muscular dystrophy type 1, caused by mutations in the calpain 3 gene, is the most common limb-girdle muscular dystrophy worldwide. Recently, cases of autosomal dominant calpainopathy have been described. A man was referred to our neurological outpatient clinic at the age of 54 for persistent hyperCKemia (>1000 U/l) associated with muscle fatigue and myalgia. Clinical examination revealed mild proximal weakness in the lower limbs. His brother exhibited a moderate increase in serum creatine kinase levels (up to 2000 U/l) without other signs of myopathy. Their father experienced slowly progressive lower limb weakness after the age of 50. The calpain 3 variant c.1478G>A (p.Arg493Gln) in the heterozygous state was identified in both brothers. In silico modeling studies predict that this substitution may disrupt protein folding. This represents the first description of the heterozygous p.Arg493Gln calpain 3 variant as a potential cause of mild calpainopathy.